Editorial: do thiopurines and biologics decrease the risk of colectomy?. Issue 9 (11th October 2017) - H Allin, K.; Jess, T.
Abstract : This article is linked to Eriksson et al papers. To view these articles visithttps://doi.org/10.1111/apt.14268 andhttps://doi.org/10.1111/apt.14336 .